The Challenges of Tachycardia Induced Cardiomyopathy - a Case Report - Andreea Elena VELCEA; Maria Claudia Berenice SURAN; Dragos VINEREANU (Sciendo, 2021)
Tachycardia-induced cardiomyopathy (TIC) is characterized by reversible left ventricular dysfunction caused by long-standing tachycardia. Treatment options for tachyarrhythmias causing TIC have evolved, especially the rhythm control strategies, ensuring a better and more sustainable control of the arrhythmia. We report the case of a 46-year-old male presenting with acute heart failure, atrial fibrillation (AF) of unknown duration and severe left ventricular dysfunction, as well as left ventricular dilation. His medical history was relevant for atrial flutter treated with catheter ablation, hypertension, and frequent atrial ectopy for which he had been prescribed amiodarone. Coronary artery disease and other potential causes for left ventricular dysfunction were excluded with coronary angiography and cardiac magnetic resonance. Thus, the patient had a high suspicion of TIC. We opted for a rhythm control strategy, however, after a successful initial electrical cardioversion, he had AF recurrence a few days later, under classic heart failure medication and antiarrhythmics. Pulmonary vein isolation was then performed, with no complications. At the one-month follow-up visit the patient was arrhythmia-free and had a normal left ventricular ejection fraction, with a slightly enlarged left ventricle. We opted to continue the heart failure medication. This case illustrates a typical case of AF induced TIC and the limited pharmacological options that exist for rhythm control, as well as the high efficacy of catheter ablation and value of imaging.